Quality of life and its associated factors among elderly residents in FELDA settlements in Johor, Malaysia - Azam, Syafinas (2017)
Introduction: Quality of Life (QoL) was an important concern in health status, social factors and economics of developing country like Malaysia. As Malaysia is moving towards a rapidly developing economy, its elderly populations are also expected to increase in their life expectancy. With life expectancy is increasing, QoL is declining with age. Many factors may affect elderly QoL but it is not clear whether these factors such as socio-demographic, health-related, lifestyle, psychosocial, functional, anthropometry characteristics and biochemical parameters will improve QoL. There were eight domains and two component summary of QoL. Objective: This study was conducted to determine the associated factors of QoL among Malay elderly residents at FELDA Schemes in Johor Malaysia. Methodology: This was a cross-sectional study which involved a total of 269 respondents (130 men and 139 women) with mean age 69.50±5.22 years in three selected FELDA Schemes. Subjects were sampled using probability proportionate to size (PPS) sampling. Age, sex, financial dependency, monthly income, chewing and vision problem, marital status, living arrangement and social engagement were measured using questionnaire developed by researcher. Sleep quality was measured with Pittsburgh Sleep Quality Index(PSQI), appetite with Simplified Nutritional Appetite Questionnaire(SNAQ), physical activity with Rapid Assessment for Physical Activity (RAPA), dietary intake with diet history questionnaire, depressive symptoms with Geriatric Depression Scale(GDS), cognitive function with Hodkinson Abbreviated Test(HAMT), hand grip strength with a dynamometer, low extremity performance(LEP) with Short Physical Performance Battery (SPPB), activity of daily living with Instrumental Activity of Daily Living (IADL), height with stadiometer, weight with weighing scale, waist circumference with measuring tape, all biochemical parameters (fasting blood sugar, lipid profile and serum albumin) were measured through respondent’s fasting blood and QoL with Short Form-36(SF-36). The findings from diet history were analyses by using Nutritionist Pro version 2.4.1 software while all data obtained from data collections were analyzed using IBM SPSS statistics version 22 software. The data collection involve face to face interview by house to house visits however data collection that involved biochemical parameters, were done at main hall in selected FELDA schemes. Result: The highest mean score of QoL was in Role Limitations due to Emotional Problems domain (94.67±20.58) and the lowest mean score was in Physical Functioning domain (70.91±27.16). LEP was the stronger significant determinant for Physical Functioning domain (β=0.300), Role Limitations due to Physical Health domain (β=0.335), Energy/Fatigue domain (β=0.277), Emotional Well Being domain (β=0.302), Social Functioning domain (β=0.311), Physical Component Summary (β=0.219) and Mental Component Summary (β=0.193) while Role Limitations due to Emotional Problem domain (β=-0.264), depressive symptoms was the strongest determinant, followed by General Health domain, sleep quality (β=-0.274) was the strongest determinant and appetite was the strongest determinant (β=0.218) for Pain domain. None of dietary factors had significant relationships with QoL. Conclusion: In conclusion, LEP was the most salient determinant of QoL. Interventional programs which targeting the physical health could appropriate be plan and implement in FELDA schemes with the efforts to maintaining the high level of LEP which will give impact on the QoL level among the FELDA elderly.